ЭПИТЕТ КАК ИЗОБРАЗИТЕЛЬНО-ВЫРАЗИТЕЛЬНОЕ СРЕДСТВО В ТЕКСТЕ РОМАНА «МАМАН БИЙ ӘПСАНАСЫ» - Абдалиева, Г.Р. (SCIENCE and SOCIETY, 2023)
In this article, the epithet is considered as a pictorial means of the literary text of the writer T. Kaipbergenov. The study was conducted on the material of the novel by T. Kaipbergenov " Маман бий әпсанасы " ("The Tale of Maman biy")
Keywords: literary text; epithet; metaphorical epithet; figurativeness; reception of injection of epithets